Evaluation of the Carbon Footprint of Rubberwood Lumber Production in Ghana - Eshun, John Frank; Marfo, Eric Donkor Marfo; Quartey, Gladys Ama (European Journal of Applied Sciences, 2022)
A key source of wood for Ghana's timber sector is rubberwood. The characteristics and economic sustainability of rubberwood for the production of wood products with added value have been the subject of numerous studies. However, rubberwood and its environmental performance, as well as green labelling, which measures carbon footprint, are not well documented in Ghana. This study assessed the carbon footprint of timber production from rubberwood using the life-cycle approach. The cradle-to-gate method was applied where the study's key findings show that Ghana's production of rubberwood lumber has a carbon footprint of 158 kg/m3CO2-eq. This resulted from the adoption of processing technologies that were inefficient and produced significant waste and emissions both at the harvesting and in the milling stages. As a result, this study demonstrated that rubberwood timber has a significant carbon footprint, and efforts must be made to advance technology and reduce waste and emissions by considering rubberwood as a green material.